2023
DOI: 10.3389/fmed.2023.1170331
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling complex relationships between COVID-19 risk factors using machine learning based models for predicting mortality of hospitalized patients and identification of high-risk group: a large retrospective study

Mohammad Mehdi Banoei,
Haniyeh Rafiepoor,
Kazem Zendehdel
et al.

Abstract: BackgroundAt the end of 2019, the coronavirus disease 2019 (COVID-19) pandemic increased the hospital burden of COVID-19 caused by the SARS-Cov-2 and became the most significant health challenge for nations worldwide. The severity and high mortality of COVID-19 have been correlated with various demographic characteristics and clinical manifestations. Prediction of mortality rate, identification of risk factors, and classification of patients played a crucial role in managing COVID-19 patients. Our purpose was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Most current studies using ML techniques confirm that respiratory parameters like SpO 2 and the need for invasive ventilatory support are considered the most important predictors for mortality in hospitalized COVID-19 patients treated with remdesivir. While hypertension and worsening renal function are also considered mortality predictors in these studies, they did not hold enough significance in our research [81,82]. Kuno T et al developed a predictive model for in-hospital mortality using ML methods in COVID-19 patients treated with steroids and remdesivir.…”
Section: Discussionmentioning
confidence: 75%
“…Most current studies using ML techniques confirm that respiratory parameters like SpO 2 and the need for invasive ventilatory support are considered the most important predictors for mortality in hospitalized COVID-19 patients treated with remdesivir. While hypertension and worsening renal function are also considered mortality predictors in these studies, they did not hold enough significance in our research [81,82]. Kuno T et al developed a predictive model for in-hospital mortality using ML methods in COVID-19 patients treated with steroids and remdesivir.…”
Section: Discussionmentioning
confidence: 75%
“…Some of them agree that advanced age is a high-risk factor for mortality [19][20][21]. Banoei et al determined that saturation level and loss of consciousness were also risk factors [22]; Kumaran et al indicated that it was respiratory difficulties [19]; Nieto-Codesido et al concluded that acute phase reactants had a high level of importance in poor prognoses [20]; and Izquierdo et al reported that fever was the second most important predictor after age [23]. These studies, like others, may differ in various aspects such as the ML model used, the time interval analyzed, and/or the variables studied.…”
Section: Introductionmentioning
confidence: 99%
“…Most proposed models or systems have not been tested on other datasets. It is also noted that even though the COVID-19 datasets have become more available, most have not been validated and can be subject to mislabeling, noise, incompleteness, corruption, or low quality [46][47][48][49]. One relevant question is how these models or systems that have been trained on one training database will perform on other datasets that inevitably have certain disparities.…”
Section: Introductionmentioning
confidence: 99%